2020
DOI: 10.7554/elife.57410
|View full text |Cite
|
Sign up to set email alerts
|

Signaling diversity enabled by Rap1-regulated plasma membrane ERK with distinct temporal dynamics

Abstract: A variety of different signals induce specific responses through a common, extracellular-signal regulated kinase (ERK)-dependent cascade. It has been suggested that signaling specificity can be achieved through precise temporal regulation of ERK activity. Given the wide distrubtion of ERK susbtrates across different subcellular compartments, it is important to understand how ERK activity is temporally regulated at specific subcellular locations. To address this question, we have expanded the toolbox of Förster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 67 publications
2
50
0
Order By: Relevance
“…Second, we simulated Ras or Rap knockout and measured ERK activity after LTP induction. Simulation results are consistent with experimental data ( Grewal et al, 2000b ; Grewal et al, 2000a ; Keyes et al, 2020 ; Li et al, 2016 ; Takahashi et al, 2013 ; York et al, 1998 ; Zhang et al, 2018 ) as knocking out Rap1 produces a greater ppERK deficit than knocking out Ras ( Figure 8—figure supplement 4B ). We assessed whether Ras could compensate for Rap and vice versa, by doubling the quantity of the remaining GTPase.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Second, we simulated Ras or Rap knockout and measured ERK activity after LTP induction. Simulation results are consistent with experimental data ( Grewal et al, 2000b ; Grewal et al, 2000a ; Keyes et al, 2020 ; Li et al, 2016 ; Takahashi et al, 2013 ; York et al, 1998 ; Zhang et al, 2018 ) as knocking out Rap1 produces a greater ppERK deficit than knocking out Ras ( Figure 8—figure supplement 4B ). We assessed whether Ras could compensate for Rap and vice versa, by doubling the quantity of the remaining GTPase.…”
Section: Resultssupporting
confidence: 84%
“…Thus, our model predicts that an Epac knockout would lead to slower ERK activation. These different time frames of ERK may phosphorylate different targets ( Keyes et al, 2020 ; Zhai et al, 2013 ; Zhang et al, 2018 ). For example, Epac, a molecule of emerging importance in neurodevelopmental disorders, may have a role in disorders in cAMP degradation by enhancing the early activation of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…While the median puncta lifetime observed via TIRF imaging was <1 min (fig. S3, B and C), the isoproterenol-induced response from clathrin-targeted FluoSTEP-ICUE was largely sustained over 20 min [sustained activity metric ( 46 ) 20 min after stimulation (SAM20) = 0.90 ± 0.019, n = 55 cells; see Materials and Methods] ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding p-ERK, it is known that there are mitochondrial substrates for its kinase activity [34]. Recent data underlines that ERK signaling specificity requires spatial compartmentalization of ERK activity for signals like EGF to govern diverse functional responses via compartmentalized ERK activity [35]. Previous data showed that p-ERK mitochondrial location could be a consequence of tumoral transformation [36] demonstrating that a fraction of active ERK1/2 associates with succinate dehydrogenase and some mitochondrial chaperones, such as TRAP1 [37].We have previously shown that motor neurons in spinal cord from ALS patients exhibit p-ERK aggregates in extranuclear locations [7].…”
Section: Discussionmentioning
confidence: 99%